Alpha-tocopherol improves sperm quality by regulate intracellular Ca2+ intensity (influx/efflux) of Simmental bull cattle sperm - Hermin Ratnani; Suprayogi TW; Sardjito T; Susilowati S; Azura S (MDPI AG, 2020)
Background: The effects of α-tocopherol on intracellular Ca2+ intensity in semen cryopreservation by regulate intracellular Ca2+ intensity have not been reported yet. Objective: The research was conducted to evaluate the effect of supplementation α-tocopherol into egg yolk skim milk extender on sperm quality and intracellular Ca2+ intensity. Methods: Semen samples were collected and supplemented with respectively 0mM (P0); 0.5mM (P1); 1mM (P2); 1.5mM (P3) and 2mM (P4) α-tocopherol in extender before cryopreservation processes. Post-thawing sperm was evaluated for motility, viability, and abnormality using Phase Contrast Microscope (200x) with eosin-nigrosine staining, and intracellular Ca2+ intensity of the best result dose was evaluated using Confocal Laser Scan Microscope (400x) with Fluo-3 Staining. Results: The results showed there was a significant difference (P≤0.05) in sperm motility and viability between P0; P1 with P2; P3; P4. The Motility and viability between groups P0; P1 and P3; P4 showed no significant difference (P≥0.05), while P2 with P3; P4 showed significant difference (P≤0.05). There was a significant difference (P≤0.05) in sperm abnormality of P0; P1 with P2; P3; P4. The abnormality between P0; P1 and P2; P3 showed no significant difference (P≥ 0.05), while P2; P3 showed a significant difference with P4 (P≤0.05). The best result in sperm quality was supplementation with 1.5mM α-tocopherol. Ca2+ intracellular intensity: 142.76 ± 21.8 au (P0) and 176.06 ± 61.43 au (P3). Conclusions: It was concluded that 1.5mM α-tocopherol is the best dose to improve sperm quality by regulating intracellular Ca2+ intensity on Simmental bull cattle.